2023
DOI: 10.1039/d2ew00737a
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of intra- and inter-lab variability in quantifying SARS-CoV-2 in a state-wide wastewater monitoring network

Abstract: In December 2019, SARS-CoV-2, the virus that causes coronavirus disease 2019, was first reported and subsequently triggered a global pandemic. Wastewater monitoring, a strategy for quantifying viral gene concentrations from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
2
0
0
Order By: Relevance
“…In general, the average N2 gene fragments/L spanned 1.5 log 10 among the laboratories in the network during each trial (range, 0.7-2.2 log 10 ). 22 Like other studies, some network laboratories observed differences between N1 and N2 gene fragment copies/L, while other laboratories did not see differences between these 2 N markers. 12,15,[23][24][25][26][27] In July 2022, the OCWMN transitioned the sample analyses from the multiple research laboratories to ODH Public Health Laboratory (PHL).…”
Section: Laboratory Analytical Methods Groupsupporting
confidence: 53%
See 1 more Smart Citation
“…In general, the average N2 gene fragments/L spanned 1.5 log 10 among the laboratories in the network during each trial (range, 0.7-2.2 log 10 ). 22 Like other studies, some network laboratories observed differences between N1 and N2 gene fragment copies/L, while other laboratories did not see differences between these 2 N markers. 12,15,[23][24][25][26][27] In July 2022, the OCWMN transitioned the sample analyses from the multiple research laboratories to ODH Public Health Laboratory (PHL).…”
Section: Laboratory Analytical Methods Groupsupporting
confidence: 53%
“…From the point of network initiation until December 2021, 8 split-sample trials were performed. In general, the average N2 gene fragments/L spanned 1.5 log 10 among the laboratories in the network during each trial (range, 0.7-2.2 log 10 ) 22. Like other studies, some network laboratories observed differences between N1 and N2 gene fragment copies/L, while other laboratories did not see differences between these 2 N markers 12,15,23–27…”
Section: Contextsupporting
confidence: 50%